The Role of Social Capital in Developing Smallholders’ Beef Cattle in Bengkulu - Ishak, Andi; Ramon, Erpan; Efendi, Zul; Wulandari, Wahyuni Amelia; Kusnadi, Harwi; Fauzi, Emlan; Sastro, Yudi (Sodality: Jurnal Sosiologi Pedesaan, 2021)
The government continues developing the smallholder beef cattle through various programs to reduce beef imports and increase farmers’ income. This research aims to describe the role of social capital at the farmer group level in the development of smallholder beef cattle in Bengkulu. The research was conducted from August to December in 2020 with an in-depth interview method involving 3 farmer groups receiving beef cattle aid from the Department of Animal Husbandry and Animal Health of Bengkulu Province. The identification of social capital (norms, trusts, and networks) that affects the development of livestock populations and increases the capacity of farmer groups is analyzed descriptively using an interactive model. The results show that social capital has an important role in developing the capacity of the farmer groups to manage livestock aid, namely (1) the norm of raising livestock with a profit sharing system causes an increase farmer group’s livestock population, (2) the trust of farmer groups members is influenced by social ties and the role of farmer group leader, and (3) a good network of cooperation within farmer groups increases social capital and livestock population.